Drawing a Graph in a Hypercube - Wood, David R. (The Electronic Journal of Combinatorics, 2006)
A d-dimensional hypercube drawing of a graph represents the vertices by distinct points in {0,1}^d, such that the line-segments representing the edges do not cross. We study lower and upper bounds on the minimum number of dimensions in hypercube drawing of a given graph. This parameter turns out to be related to Sidon sets and antimagic injections.